Could Syria be next? Protests by Arab internet bloggers - Zulkifli Bin Mohamed Sultan (2016)
Recent political unrest in the Middle East showed numerous dissatisfactions with the style of governance which seek to dictate and control its people. The detention of a young Syrian blogger has aroused the Arab blogosphere to protest against such suppression.